Linearly Manipulating Color Emission via Anion Exchange Technology for High Performance Amplified Spontaneous Emission of Perovskites - Liu, Nian (Advanced materials (Deerfield Beach, Fla.), 2024)
© 2023 Wiley-VCH GmbH.